Food Security Analysis of Shallot Farmer Household During the Covid-19 Pandemic in Probolinggo Regency (A Case Study on Shallot Farmer Household in Mranggonlawang Village, Dringu District, Probolinggo Regency) - Rohmatul Khasanah, Ulfa; Nira Praditya Sari; Nuhfil Hanani; Fahriyah; Condro Puspo Nugroho; Syafrial; Rosihan Asmara (HABITAT, 2022)
The Covid-19 pandemic has had an impact on the agricultural sector, both in terms of trade, prices, and the decline in farmers' income levels. Amid the COVID-19 outbreak, food security is something that the government must pay attention to so that there is no food crisis. If farmer households have not realized food security, it won't be easy to create food security at higher levels such as the village, district, provincial, and national levels. This study aims to analyze food security based on EAR and SFE values ​​and determine the effect of socioeconomic factors on household resilience. Determination of the research location was determined purposively, and the number of samples was taken by cluster sampling. The analytical method uses the Jonnson and Toole model to determine household food security and multiple linear regression analysis to determine the effect of socioeconomic factors on EAR. The results of the food security analysis show that 51.7% of households with energy consumption >80% and expenditure of 60% are categorized as food vulnerable. The results of the analysis of socio-economic factors that can affect EAR are income, number of dependents in the family, length of education of housewives, and age of the head of the family with a confidence level of 80%. The analysis results show that most shallot farming households are in a food-insecure state.